Designing Motion Graphics for Social Media Content in Yeobo Toppoki Branding - Rinaldi, Mario; Pertiwi, Annisa Bela; Budiman, Budiman; Farid, Rudy; Benyamin, Muhammad Firdaus (LPPM Institut Seni Indonesia Padangpanjang, 2024)
In the current digital era, a brand requires various captivating ideas to convey a message to its audience. The rapid development of information presentation technology is evident with the presence of various media with their respective characteristics and advantages. Through promotional media, the public can receive clear information about products offered by a company or organization. With the increasing number of internet users, the exchange of information has become faster and easier, leading people to prefer communication through the internet as it facilitates communication without time, place, and distance constraints. This ease has led millions of people worldwide to interact using the internet, giving rise to the formation of social media sites. Alongside the evolution of information presentation, the use of motion graphics also provides its own allure as a promotional medium to the audience. Promotional media utilizing motion graphic techniques ensures that all presented information is quickly understood, as the information is conveyed visually and audibly. The creation of motion graphics has become an effective method for producing content for social media. The process of creating motion graphics for social media content involves collaboration among creative teams, graphic design, animation, and editing, making it the focus of research as a model for developing media applications. This design employs a qualitative descriptive research method with a SWOT approach to identify the main potentials to be highlighted. The objective of this design is to create a motion graphic capable of displaying information and attractive potentials for the Yeobo Toppoki brand so that the audience becomes familiar with the packaging and various variants of the brand.